THE ROLE OF THE LOAMY ELEMENT IN THE PROCESS OF COMPRESSION OF SATURATED DISPERSIVE SOILS UNDER TEMPERATURE CHANGE - SHOSTAK, А. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
This paper considers the major results of numerous experiments aimed at the study of compressibility and filtrational consolidation process in some types of loam soils. The experimental data allow for theoretical conclusions on the importance of the loamy element and its role in the process of solidification and consolidation.